Сучасний стан і тенденції розвитку електроенергетики України - Білоцерківський, Олександр Борисович; Ширяєва, Наталя Володимирівна (НТУ "ХПІ", 2015)
У статті досліджено сучасний стан та тенденції розвитку електроенергетики України. Розглянуто виробництво електроенергії в Україні за 2001-2014 рр. Розраховано аналітичні показники ряду динаміки. Побудовано одночленні та двохчленні регресійні моделі. Перевірено неавтокорельованість залишків, використовувався критерій Неймана. Зроблено точковий прогноз виробництва електроенергії на 2015 і 2016 роки.

In the article the current state and trends of electro-energy in Ukraine are considered. Ukrainian electro-energy production for time period from 2001 till 2014 is analyzed. Basis and chain time series parameters were analytically calculated, using methods of statistics. It was concluded that the highest energy production growth rate was in 2010 and the lowest one was in 2009. For further investigation one- and two-term autoregressive models were constructed. These models were chosen as they most adequately describe the changes over time of time series indicators. It was shown that the second model term has a little affect on the calculation results.
Current state and trends of electro-energy in Ukraine
Keywords: критерій Неймана; точковий прогноз; неавтокорельованість залишків; electro-energy; Neumann criteria; methods of statistics; point forecast